KARAKTERISASI HIDROKSIAPATIT DARI TULANG IKAN CAKALANG (Katsuwonus pelamis) DENGAN ANALISIS X-RAY FLUORESENCE MENGGUNAKAN METODE PRESIPITASI - pe william, halisca clara; Syam, Syamsiah; Aslan, Sarahfin; Amran, Ardian Jayakusuma; Arifin, Nurfadillah (YARSI Dental Journal, 2025)
Background: Indonesia's vast marine waters provide a diverse range of fish species, one of which is skipjack tuna (Katsuwonus pelamis). The fish processing industry generates various types of waste, including fish bones, which contain high calcium levels and can produce 60–70% hydroxyapatite, commonly used for dental remineralization. One method for synthesizing hydroxyapatite is the precipitation method, which can be analyzed using X-Ray Fluorescence (XRF) to determine the characterization of hydroxyapatite from skipjack tuna bones. Objective: To characterize hydroxyapatite from skipjack tuna (Katsuwonus pelamis) bones using X-Ray Fluorescence analysis with the precipitation method. Materials and Methods: This study employed a laboratory experimental design. The primary material used was skipjack tuna (Katsuwonus pelamis) bone waste, processed using the precipitation method for 7 hours, followed by X-Ray Fluorescence (XRF) analysis. Results: Based on X-Ray Fluorescence (XRF) analysis, the precipitation method revealed that skipjack tuna bones contained 57.98% calcium and 38.78% phosphorus. Conclusion: This study confirms that skipjack tuna bones contain calcium and phosphorus, making them a potential raw material for hydroxyapatite synthesis.